Regional Integration and Production Divisions in Malaysia - Hasan, Sharina Farihah (Journal of Architecture, Planning and Construction Management, 2020)
Globalization increases world-wide integration of markets for goods, services, labor, and capital. It seems to dominate discussions on the direction of social change and representations of the world. This study is no exception; it provides an overview on the economic aspects of globalization. It mainly focuses on economic integration, trade patterns of multinational firms and international labor movement. As part of the analysis, international labor movement is centered on the inflow of unskilled labor into host country and the effects they bring along to the welfare of local populations. Particular attention is also given to the construction sector. The main aim of this study is to discuss economic integration, production divisions and international labor movement as parts of globalization. The study also aims to evaluate and examine international labor movement and provide analysis using Computable General Equilibrium modeling approach on labor movement policy in Malaysia. The objectives of the study are: (i) to investigate the effect of foreign labors on the relative price, the wage rate, and the welfare of native inhabitants in the host country; (ii) to discuss the trade pattern of heterogeneous firms by examining the allocation production behavior of multinational firms using general equilibrium approach; (iii) to describe the Computable General Equilibrium (CGE) modeling approach on international labor movement issues by adopting GTAP model and data base; and (iv) to conduct analysis on the effect of international labor movement policy, Malaysia as a case study. The methodology adopted for the study is theoretical general equilibrium and global comparative statics which are commonly applied in policy analysis. Two-country, five-sectors and five-factors model is formulated to theoretically signify international labor movement scenario into Malaysia. Assumptions are made for simplification of analysis. Considering Malaysia’s high reliance on unskilled migrant labor, the model assumed that inflows of foreign labor only involve this type of labor and therefore international movement of skilled labor and issue of brain drain is ignored. The assumptions together with the equations represent basic framework for simulation process using specialized software (GEMPACK software). Data aggregation for analysis is generated from GTAP 7 Data Base. However, the model necessitates further data to complement GTAP 7 Data Base in order to simulate GMig2 model. In addition, downloadable data base for GMig2 model is not sufficient for Malaysia-ROW model. Additional ad hoc data was formulated before proceeding with simulation process. Results of the simulation are discussed in two parts. Part 1 looks at the effects of increasing inflow of unskilled foreign labor into Malaysia from year 2005 till 2010. The result indicates that with the rising numbers of such labor, Malaysian economy gains in term of increasing returns to capital and tax incomes. Although unskilled local labor is experiencing decreasing real wage, total welfare of Malaysian population eventually increases. This could be due to the fact that permanent residents would start trading with foreign labors and increase the aggregate welfare. On the other hand, Part 2 of the results which discussed the policy implementation of reducing the number of unskilled foreign labor to 1.5 million by 2010 showed reverse effects. This would cause GDP to fall and reduction in total income, thus decreasing total welfare of the country’s population. Construction sector being the sector that is labor-intensive, is inevitably affected by the inflow of foreign labors. The sector is highly dependent upon foreign labor due to its nature of work that in general tends to shun locals. Results show that the firm price of unskilled labor decreases with the increase supply of labor, hence creating more demand for the labor. With policy implementation however, the lower decreases in firm price eventually reduce construction output. Assuming that the number of unskilled foreign labor to be reduced to 1.5millon by 2010, Malaysian economies would loss from decrease returns to capital and decrease tax incomes while ROW economies loss from the decrease in remittances and wages. Kyoto University, Japan